PEMAKAIAN BALING-BALING BEBAS PUTAR (FREE ROTATING POPELLER) PADA KAPAL - Eko Julianto Sasono (TEKNIK, 2009)
Propeller as a means of ship activator expand in phase for the shake of phase. Although that way in this timepropeller represent the mechanical ship activator appliance is which is at most used for the ship of from allsize measure and its type. Pursuant to the reason is above need of research and attempt to increase efficiencyof propulsi ship. One of research and attempt which have been done/conducted by free propeller turn around.Which free propeller turn around this exploit the free energi stream rotation (slip stream) from especialpropeller, while as ordinary propeller of this propeller can alter from free stream into energi push ( trusht )